2015
DOI: 10.3126/dsaj.v9i0.14021
|View full text |Cite
|
Sign up to set email alerts
|

Livelihood Change and Household Strategies: Social Displacement of the Upper Class in Dhading

Abstract: This article examines livelihoods transition among agrarian households in a cluster of villages adjacent to Kathmandu in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…In Nepal, where the rural-urban migration figure stood at 2.6 million in 2011 (KC 2003), migration is seen as the gateway allowing individuals access to resources and opportunities that cannot be found in their own communities. Rural youth who aspire education beyond secondary school are compelled to migrate to the city (Luintel 2015). The capital Kathmandu-home to 980,000 inhabitants (Central Bureau of Statistics 2020)-has the highest number of migrants (Luintel 2015).…”
Section: Rural-urban Migration For Education and Work In Nepalmentioning
confidence: 99%
See 2 more Smart Citations
“…In Nepal, where the rural-urban migration figure stood at 2.6 million in 2011 (KC 2003), migration is seen as the gateway allowing individuals access to resources and opportunities that cannot be found in their own communities. Rural youth who aspire education beyond secondary school are compelled to migrate to the city (Luintel 2015). The capital Kathmandu-home to 980,000 inhabitants (Central Bureau of Statistics 2020)-has the highest number of migrants (Luintel 2015).…”
Section: Rural-urban Migration For Education and Work In Nepalmentioning
confidence: 99%
“…Rural youth who aspire education beyond secondary school are compelled to migrate to the city (Luintel 2015). The capital Kathmandu-home to 980,000 inhabitants (Central Bureau of Statistics 2020)-has the highest number of migrants (Luintel 2015). A World Bank (2016) report revealed that young people (aged 15-40) make up 40% of the total Nepali population and a few years earlier, in 2011, the Census Bureau of Statistics recorded Kathmandu as having the highest youth population nationwide-some 52.9% (KC 2003).…”
Section: Rural-urban Migration For Education and Work In Nepalmentioning
confidence: 99%
See 1 more Smart Citation
“…Subedi and Pandey (2002) Livelihood strategies of Rai communities in the Arun Valley: continuity and change, Subedi et al (2007) studied crop-based subsistence agriculture, supplemented by remittances and off-season farming, as a means of livelihood in mid-western Nepal. Luintel (2015) studied "Livelihood Change and Household Strategies: Social Displacement of the Upper Class in Dhading, Pandey (2017) studied life and livelihoods in the 'Forbidden Kingdom, "the Trans-Himalayas, Nepal, Panta (2021) studied the livelihood pattern of Gandharva in Baglung, Nepal. Besides these research efforts, many considerable studies have been carried out in Nepal, but for the livelihood systems of the Majhi in Baglung, Nepal, there is a unique spatial gap that is not covered.…”
Section: Introductionmentioning
confidence: 99%